"Rocks" or "Islands"? Sailing Towards Legal Clarity in the Turbulent South China Sea. (2016) - Oral, Nilufer
Abstract : The Arbitral Award handed down by the Permanent Court of Arbitration (PCA) on 12 July 2016 in In the Matter of the South China Sea Arbitration between the Republic of the Philippines and the People's Republic of Chinais undoubtedly one of the most anticipated decisions in recent memory.